From clusters to entrepreneurial universities and vice versa: ways of developing the local economy: a systemic approach. (2018) - Gagnidze, Ineza
This paper describes means of developing the local economy. There are 3, 000 strong clusters across Europe and the model of the entrepreneurial university is the most successful to date. At different times since 1990, clusters and entrepreneurial universities have become more popular as tools for developing the local economy. As a result, their research continues in separate and independent directions. Attempts to discuss these two tools together are uncommon in the academic literature. In this paper, we will discuss the systemic links between the mutual influence of clusters and entrepreneurial universities.